Constructivism and Its Implications for Curriculum Development in the Philippines (London Journal of Research In Humanities and Social Sciences, 2025)
The paper examines constructivism as a learning theory and its influence on curriculum development in the Philippines, particularly within the framework of the K to 12 Enhanced Basic Education Program. It draws from the foundational contributions of Piaget, Bruner, Dewey, and Vygotsky, highlighting learner-centered approaches that emphasize inquiry, collaboration, and authentic learning. It also discusses implications for pedagogy, assessment, and teacher training, advocating for a shift from knowledge transmission to knowledge creation in Philippine education. This paper highlights how constructivist principles inform student-centered teaching strategies, authentic assessment practices, and the evolving role of teachers as facilitators rather than mere transmitters of knowledge. Furthermore, this paper emphasizes the need for sustained teacher training, authentic assessments, and the cultural adaptation of constructivist practices in order to maximize their impact on Philippine education
Keywords: curriculum development; Constructivism; Philippine Education; student-centered